2009
DOI: 10.1111/j.1365-2095.2008.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in commercial sources of soybean meal influences the severity of enteritis in Atlantic salmon (Salmo salarL.)

Abstract: Soybean meal (SBM) is a potential alternative for the replacement of fishmeal in aquafeeds. In Atlantic salmon, however, dietary SBM causes an inflammation of the distal intestine, known as SBM-induced enteritis. The objective of the present study is to verify whether different (geographically spread) commercial sources of SBM yield contrasting inflammatory responses. To do so, six SBM batches from different origins were included in the Atlantic salmon diets at the level of 20%. After 4 weeks of feeding, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 21 publications
6
41
0
4
Order By: Relevance
“…Previous studies have shown that different sources of SBM can result in differential severity of SBM-induced enteritis (Uran et al, 2008). In the present study, the mRNA expression levels of poTRY were higher in 0.4% of dietary SBS or 0.4% of dietary PA than those in 0.0% of dietary SBS or PA (Figs.1A, 2A).…”
Section: Discussionsupporting
confidence: 36%
“…Previous studies have shown that different sources of SBM can result in differential severity of SBM-induced enteritis (Uran et al, 2008). In the present study, the mRNA expression levels of poTRY were higher in 0.4% of dietary SBS or 0.4% of dietary PA than those in 0.0% of dietary SBS or PA (Figs.1A, 2A).…”
Section: Discussionsupporting
confidence: 36%
“…Despite the high dietary levels of SBM (29–80% SBM) and the relatively long feeding period (8 weeks) used in the present study, we did not observe major tissue disruption in any of the intestines examined. Although the severity of enteritis has been shown to fluctuate with factors such as water temperature or commercial source of SBM (Uràn et al., 2008b, 2009), based on our observations, it appears that sunshine bass are relatively tolerant of SBM in the diet with respect to maintenance of gut integrity and function.…”
Section: Discussionmentioning
confidence: 70%
“…The replacement of fish meal by soybean meal (SBM) resulted in an inflammation of the endgut of Atlantic salmon [53,195,196], and the severity was dependent on the amount and strain of soya used [197]. The animals showed normal growth and feed intake, however they developed a severe inflammation in the second gut segment characterized by: the disappearance of the supranuclear vacuoles (SNV) in the second segment enterocytes, a strong decrease of microvilli height, a swelling of the lamina propria and subepithelial mucosa, an increase in the number of goblet cells, a strong invasion of the eosinophilic granulocytes, a loss of the mucosal fold architecture and finally a total tissue disruption [53,195,196] and when SBM feeding is continued for 4 months the chronic intestinal inflammation even resulted in adenocarcinoma development with liver metastases [198].…”
Section: Enteritis Models In Fishmentioning
confidence: 99%